Lactoferrin reduces the risk of respiratory tract infections: A meta-analysis of randomized controlled trials. (October 2021) - Ali, Akbar Shoukat; Hasan, Syed Shahzad; Kow, Chia Siang; Merchant, Hamid A.
Summary: Background: Lactoferrin (Lf) is one of the key immunomodulatory substances found naturally in various body fluids, such as saliva, tears, and breast milk, and forms a vital part of the innate defense against invading pathogens. Various studies have demonstrated antibacterial, antifungal, and antiviral properties of Lf and its protective role against respiratory tract infections (RTIs). The present meta-analysis aims to elucidate the association of Lf administration in reducing the risk of RTIs by systematically reviewing the data from randomized controlled trials (RCTs). Methods: We systematically searched PubMed, Cochrane Library, Medline & CINAHL, Turning Research into Practice (TRIP), ProQuest Theses & Dissertations Databases, and China National Knowledge Infrastructure (CNKI) from inception till March 15, 2021. The primary outcome measure was a reduction in respiratory illness; decrease in frequency, symptoms, and duration. Random-effects model was used to estimate the odds ratio (OR) and 95% confidence interval (CI). We used Cochrane's RoB-2 to appraise the risk of bias of included RCTs. Results: A total of nine RCTs were eligible for this review, of which six were included in the meta-analysis. Overall, two studies demonstrated a high risk of bias. The meta-analysis revealed a significantly reduced odds of developing respiratory infections with the use of Lf relative to the control (pooled odds ratio = 0.57; 95% confidence interval 0.44 to 0.74, n = 1, 194), with sufficient evidence against the hypothesis of 'no significant difference' at the current sample size. Conclusions: The administration of Lf shows promising efficacy in reducing the risk of RTIs. Current evidence also favours Lf fortification of infant formula. Lf may also have a beneficial role in managing symptoms and recovery of patients suffering from RTIs and may have potential for use as an adjunct in COVID-19, however this warrants further evidence from a large well-designed RCT.